hws/proof.tex
changeset 388 66f66f1710ed
parent 102 1ab41c59e3d3
child 402 55f097ab96c9
equal deleted inserted replaced
387:8aa406adfde0 388:66f66f1710ed
   186 further $L(der\,c\,r) \,@\, L(r^*)$. By induction hypothesis (I) we know that is equal to 
   186 further $L(der\,c\,r) \,@\, L(r^*)$. By induction hypothesis (I) we know that is equal to 
   187 $(Der\,c\,L(r)) \,@\, L(r^*)$. (*)
   187 $(Der\,c\,L(r)) \,@\, L(r^*)$. (*)
   188 
   188 
   189 \end{itemize}
   189 \end{itemize}
   190 
   190 
   191 
       
   192 
       
   193 
       
   194 Let us now analyse $Der\,c\,L(r^*)$, which is equal to $Der\,c\,((L(r))^*)$. Now $(L(r))^*$ is defined
   191 Let us now analyse $Der\,c\,L(r^*)$, which is equal to $Der\,c\,((L(r))^*)$. Now $(L(r))^*$ is defined
   195 as $\bigcup_{n \ge 0} L(r)$. We can write this as $L(r)^0 \cup \bigcup_{n \ge 1} L(r)$, where we just 
   192 as $\bigcup_{n \ge 0} L(r)^n$. We can write this as $L(r)^0 \cup \bigcup_{n \ge 1} L(r)^n$, where we just 
   196 separated the first union and then let the ``big-union'' start from $1$. Form this we can already infer
   193 separated the first union and then let the ``big-union'' start from $1$. Form this we can already infer
   197 
   194 
   198 \begin{center}
   195 \begin{center}
   199 $Der\,c\,(L(r^*)) = Der\,c\,(L(r)^0 \cup \bigcup_{n \ge 1} L(r)) = (Der\,c\,L(r)^0) \cup Der\,c\,(\bigcup_{n \ge 1} L(r))$
   196 $Der\,c\,(L(r^*)) = Der\,c\,(L(r)^0 \cup \bigcup_{n \ge 1} L(r)^n) = (Der\,c\,L(r)^0) \cup Der\,c\,(\bigcup_{n \ge 1} L(r)^n)$
   200 \end{center}
   197 \end{center}
   201 
   198 
   202 The first union ``disappears'' since $Der\,c\,(L(r)^0) = \varnothing$.
   199 The first union ``disappears'' since $Der\,c\,(L(r)^0) = \varnothing$.
   203 
   200 
   204 
   201